Familial NEDD4L variant in periventricular nodular heterotopia and in a fetus with hypokinesia and flexion contractures. Issue 6 (4th November 2018) - Elbracht, Miriam; Kraft, Florian; Begemann, Matthias; Holschbach, Petra; Mull, Michael; Kabat, Ildiko M.; Müller, Britta; Häusler, Martin; Kurth, Ingo; Hehr, Ute
Abstract: Background: Mutations in the HECT domain of NEDD4L have recently been identified in a cohort of eight patients with a syndromic form of bilateral periventricular nodular heterotopia (PVNH) in association with neurodevelopmental delay, cleft palate, and toe syndactyly (PVNH7). Methods: Case report based on NGS sequencing. Results: Here, we describe a girl with a novel heterozygous NEDD4L missense variant, p.Tyr679His, and characteristic clinical findings, including bilateral periventricular nodular heterotopia, cleft palate and mild toe syndactyly. Molecular testing from peripheral blood identified the healthy father to carry the NEDD4L variant in mosaic state. Notably, a previous pregnancy of the couple had been terminated due to a complex fetal developmental disorder, including hypokinesia and flexion contractures. Upon review, this affected fetus was also shown to carry the familial NEDD4L variant. Conclusion: Our findings may suggest a broader spectrum of NEDD4L ‐associated phenotypes, including severe prenatal neurodevelopmental manifestations, which might represent yet another genetic form of fetal hypokinesia with flexion contractures. Abstract : Mutations in the HECT domain of NEDD4L have recently been identified in periventricular nodular heterotopia. Our findings may suggest a broader spectrum of NEDD4L ‐associated phenotypes, including severe prenatal neurodevelopmental manifestations, which might represent yet another genetic form of fetal hypokinesia with flexion contractures.